Alternative Dispute Resolution Criminal Acts Of Money Politics In Elections In View Of Normative Law - Ariman Sitompul (International Asia Of Law and Money Laundering, 2023)
The implementation of omnibus law in Indonesia, between what ideally happens and what actually happens. When the omnibus law is expected to be a powerful solution to the complexity of regulation in Indonesia, the reality is transformed into a new field of problems that reap many negative responses from various circles of society. Omnibus law which is interpreted by the government and parliament as a progressive breakthrough to overcome multisectoral problems is interpreted differently by some circles of society and academia as a flawed law, both in formal and material terms. Although the existence of omnibus law is not a new item in legal theory, its existence still sounds foreign in the constitutional dialectic of Indonesia. Therefore, the purpose of this paper is to explore the nature of omnibus law and its implementation in Indonesia.